PENGARUH PENERAPAN STRATEGI SPOTLIGHT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 LUBUK SIKAPING - Warman, Egi - (Pendidikan Matematika, 2014)
This research was background by students understanding of mathematical concept in class VIII SMP 2 Lubuk Sikaping academic year 2013/2014 that was still low, the students were not brave to perform and give their opinion in front of the class. The pupose of this research was know about students understanding of mathematical concept that used spotlight strategy better than with used conventional learning and see how students growth understanding of mathematical concept whit apply spotlight strategy at class VIII SMPN 2 Lubuk Sikaping. Type of research was experiment research, with the type of randomized trials on the subject. The form of the test was used in this research was descriptive with reliabilities test 0.950. Technic of analyze the data was used test t one side, and hypothesis test results obtained ttable value = 1.677 and t = 1.852. The hypothesis was accepted because t > ttable, there for the hypothesis was given accepted at real level Î± = 0.05. It can be concluded that students understanding of mathematical concept with apply spotlight strategy was better than students understanding of mathematical concepts with conventional learning at class VIII SMP 2 Lubuk Sikaping.